La quête d’identité professionnelle des journalistes de la presse en ligne en Algérie : Pratiques, compétences et profils - Aissa Merah (L’Année du Maghreb)
We tackle here the question of web-journalists’ professional identity in Algeria. First, we highlight the social and scientific pertinence of that theme. Then we gather theoretical elements witch allow to understand the web-journalist’s professional transition and dynamic nature of their identity. After such a methodological approach, we seize the appearance context of that press in Algeria, paying particular attention to its characters in relation with professional identity. Empirical data examine web-journalists’ social profiles and professional skills, before concluding with study’s main results.